2021
DOI: 10.3168/jds.2020-18810
|View full text |Cite
|
Sign up to set email alerts
|

Differing planes of pre- and postweaning phase nutrition in Holstein heifers: II. Effects on circulating leptin, luteinizing hormone, and age at puberty

Abstract: Increasing the preweaning plane from 5 to 10 L/d of whole milk increased serum leptin concentrations at wk 1, 3, and 5 and LH pulse amplitude, peak, and duration at wk 15. Increasing the postweaning plane from 70 to 85% of concentrate resulted in greater circulating leptin concentrations, which may be linked to an earlier onset of puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
10
1
1
Order By: Relevance
“…Circulating leptin parallels the body fat content and acts as a negative feedback regulator on feed intake [52]. However, for leptin neither the increase reported by Schwarzkopf et al (2019) [16] between week 6 to week 20 of life for calves weaned in week 16 of life, nor a difference between the high and the restricted feeding level, as shown by Bruinjé et al (2020) [53], was observed in our trial. The feeding group did not affect leptin values.…”
Section: Metabolic Hormonescontrasting
confidence: 71%
“…Circulating leptin parallels the body fat content and acts as a negative feedback regulator on feed intake [52]. However, for leptin neither the increase reported by Schwarzkopf et al (2019) [16] between week 6 to week 20 of life for calves weaned in week 16 of life, nor a difference between the high and the restricted feeding level, as shown by Bruinjé et al (2020) [53], was observed in our trial. The feeding group did not affect leptin values.…”
Section: Metabolic Hormonescontrasting
confidence: 71%
“…The increased preweaning planes of nutrition had minimal influence on growth performance postweaning, regardless of the improved indicators of growth and development in the preweaning stage. As reported in companion manuscripts (Bruinjé et al, 2019(Bruinjé et al, , 2020, increased pre-and postweaning planes of nutrition resulted in advanced reproductive development. The increased preweaning plane of nutrition resulted in enhanced LH pulses at wk 15, increased circulating leptin concentrations (Bruinjé et al, 2019), and a greater number of class 2 ovarian follicles (Bruinjé et al, 2020) during the prepubertal phase.…”
Section: Energy Provisionmentioning
confidence: 64%
“…As reported in companion manuscripts (Bruinjé et al, 2019(Bruinjé et al, , 2020, increased pre-and postweaning planes of nutrition resulted in advanced reproductive development. The increased preweaning plane of nutrition resulted in enhanced LH pulses at wk 15, increased circulating leptin concentrations (Bruinjé et al, 2019), and a greater number of class 2 ovarian follicles (Bruinjé et al, 2020) during the prepubertal phase. The increased planes of nutrition postweaning resulted in increased endometrial thickness, follicular size, number of class 3 follicles in the prepubertal phase (Bruinjé et al, 2020), greater likelihood of achieving puberty by 30 wk of age (Bruinjé et al, 2019), and increased antral follicle population in the postpubertal phase.…”
Section: Energy Provisionmentioning
confidence: 64%
See 1 more Smart Citation
“…Specifically, during the pre-weaning phase increases from 5 to 10 L/d of whole milk would rise leptin levels and LH pulses (amplitude, peak and duration) and an increased nutritional plane (from 70 to 85% concentrate) during the postweaning period would increase leptin levels. Moreover, a relation was established in which for every 1 ng/mL increase of leptin there could be a reduction of 22 days to attainment of puberty [ 88 ].…”
Section: Post-natal Developmentmentioning
confidence: 99%